(untitled) (Agro Productividad, 2025)
Objective: To analyze the perception about challenges and opportunities that women who lead agricultural cooperatives face in Colombia, and their relationship with feminine empowerment. Design/methodology/approach: A qualitative approach was used by means of the study of three cases of agricultural cooperatives, through structured interviews that addressed three dimensions: 1) sociodemographic data of producers, 2) women’s experience in cooperativism, and 3) challenges and limitations faced. Results: Important challenges were identified in feminine cooperativism, such as limited access to credit, the double workday that women practice within their households, in addition to the complexity of reconciling the demands of agricultural production with domestic responsibilities. There is also a lack of government support, scarce specialized training, and lack of accompaniment and counseling for efficiency in the commercialization of their products. Cooperativism is a platform for collective decisions and social participation, promoting leadership among women in rural zones. Limitations/implications: Some participants manifested caution when providing key information for the study. Findings/conclusions: Strategies must be generated to strengthen collective and business capacities of women, with the aim of improving the organizational and economic structure of cooperatives. Policies to promote inclusive governance, financial education, and access to new markets were suggested for a greater impact in gender equity in the sector.